Broadband and high-efficient L-shaped piezoelectric energy harvester based on internal resonance. (August 2019) - Nie, Xiaochun; Tan, Ting; Yan, Zhimiao; Yan, Zhitao; Hajj, Muhammad R.
Highlights: The theoretical model is derived with the consideration of the geometric nonlinearity of the structure and piezoelectric materials. The internal resonance response of the theoretical model is validated with ANSYS and experiments. Periodic, quasi-periodic and chaotic motions are observed. The harvested power is significantly enhanced via internal resonance: high-frequency vibration excited by low-frequency acceleration. Compared with the linear harvester, the maximum improvement of harvesting efficiency and bandwidth of nonlinear harvester are 215% and 405%, respectively. Graphical abstract: Abstract: We exploit a 1:2 internal resonance in an L-shaped beam-mass structure for broadband and high-efficient energy harvesting. The geometric nonlinearities of the structure and piezoelectric materials are introduced to establish the electromechanical-coupled distributed parameter model using the extended Hamiltons principle and Gauss law. The analytical modal shapes of the structure are derived as well. The proposed model of the energy harvester is validated with finite element simulations and experiments. Periodic, quasi-periodic and chaotic motions are observed. The tip displacement of the system is mainly determined by the first mode while the harvested power of the system is primarily derived from the second mode for internal resonances of the first and second modes. By exploiting these resonances, the harvested power is significantly improved through the low-frequency excitation exciting high-frequency vibration. The larger harvested power and smaller tip displacement are also obtained with the load resistances corresponding to the maximum global damping. Increasing the external excitation amplitude causes an increase in the frequency bandwidth over which energy can be harvested. Compared to the linear system, the L-shaped energy harvester with 1:2 internal resonance can harvest power more efficiently over a wider frequency bandwidth with reduced vibration displacement. The maximum improvement of energy harvesting efficiency and bandwidth are 215% and 405% respectively.